Gene-rich UV sex chromosomes harbor conserved regulators of sexual development - Carey Sarah B; Jenkins Jerry; Lovell JohnT; Maumus Florian; Sreedasyam Avinash; Payton Adam C; Shu Shengqiang; Tiley George P; Fernandez-Pozo Noe; Healey Adam; Barry Kerrie; Chen Cindy; et al. (AMER ASSOC ADVANCEMENT SCIENCE, 2022)
Nonrecombining sex chromosomes, like the mammalian Y, often lose genes and accumulate transposable elements, a process termed degeneration. The correlation between suppressed recombination and degeneration is clear in animal XY systems, but the absence of recombination is confounded with other asymmetries between the X and Y. In contrast, UV sex chromosomes, like those found in bryophytes, experience symmetrical population genetic conditions. Here, we generate nearly gapless female and male chromosome-scale reference genomes of the moss Ceratodon purpureus to test for degeneration in the bryophyte UV sex chromosomes. We show that the moss sex chromosomes evolved over 300 million years ago and expanded via two chromosomal fusions. Although the sex chromosomes exhibit weaker purifying selection than autosomes, we find that suppressed recombination alone is insufficient to drive degeneration. Instead, the U and V sex chromosomes harbor thousands of broadly expressed genes, including numerous key regulators of sexual development across land plants.